Holographic interferometry under phase distortions - Derzhypolska, L.A.; Gnatovskiy, O.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
An impact of non-stationary phase distortions in transfer section of a holographic interferometer on the quality of formed interference fringes in an interferogram was under investigation. A mathematical model to analyze this influence was proposed. The conclusions based on the model were made about the possibility to observe interference fringes under phase noise in the broad ranges. Theoretical estimations were involved to analyze the experimental data. For that purpose, a modified holographic interferometer scheme with regular bundle of multimode lightguiding fibers in the transfer section was used. Investigated here was the possibility to use the scheme under possible deformations of the bundle between the two interferometric exposures. Experimentally proved was the capability of the holographic interferometer with flexible lightguiding bundle to operate under reasonable deformations of the bundle and even under non-rigid fixation of bundle body.